CHALLENGES TO ENGAGING IN END-OF-LIFE CARE DISCUSSIONS AND ADVANCE CARE PLANNING - Peterson, L J (Innov Aging, 2018)
Providing end-of-life (EOL) care that aligns with individuals’ values, goals, and preferences largely depends on whether they have communicated their EOL care wishes through discussions or other forms of advance care planning (ACP). Despite the many efforts to promote ACP, large numbers of people still have not communicated their EOL wishes to others. This symposium contains five papers examining varied challenges to engagement in EOL care discussions and ACP. The first paper examines the divergence between centenarians and their proxies (N=78 dyads) on the centenarians’ EOL care planning. The second paper describes an online tool to integrate family members’ EOL care views (N=130) and examines the variability in adult children’s knowledge of their parents’ preferences. Third is a study of factors associated with whether older adults (N=364) discussed their EOL care wishes with family, focusing on the lesser likelihood of Latinos engaging in such discussions. The fourth study qualitatively explores the varied stages of readiness to engage in ACP among older Latinos with advanced disease (N=32) who participated in an ACP intervention. Finally, the fifth paper is a gap analysis of ACP interventions for individuals with cancer that uses the stages of change framework to identify underutilized processes to engage in ACP. The symposium discussant will address the challenges identified, their implications, and how to deal with them to increase EOL care discussions and ACP overall.